+0  
 
0
287
1
avatar

x^4-46x^2+45=0

Guest May 19, 2017
 #1
avatar+27044 
+2

x^4 - 46x^2 + 45 = 0

 

Let u = x^2

 

u^2 - 46u + 45 = 0

 

This factorises;  (u - 1)(u - 45) = 0

 

So 1)  u = 1       2) u = 45

 

Hence 1) x^2 = 1   so  1a) x = 1    and   1b) x = -1

 

and      2) x^2 = 45   so  2a)  x = sqrt(45) , x = sqrt(9*5),  x = 3sqrt(5)   and   2b)  x = -3sqrt(5)

.

Alan  May 19, 2017
edited by Alan  May 19, 2017

9 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.